DAMPAK KEBIJAKAN RELAKSASI PAJAK TERHADAP KEPATUHAN DAN PENERIMAAN PAJAK SELAMA PANDEMI COVID-19 - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study aims to analyse the impact of tax relaxation policies implemented by the government during the COVID-19 pandemic on taxpayer compliance and state tax revenue. Using a literature review method, this study examines literature from various sources, such as scientific journals, government reports, and official documents related to tax relaxation policies. The analysis results show that tax relaxation policies provide significant benefits for taxpayers, particularly in alleviating financial burdens and maintaining business continuity amid the economic pressures caused by the pandemic. However, the effectiveness of these policies in improving taxpayer compliance is greatly influenced by the quality of socialisation, understanding, and ease of access to digital tax services. On the other hand, tax relaxation has an impact on a decline in state revenue in the short term, even though it functions as an instrument to support the national economy and help stabilise the economy. Thus, the success of tax relaxation policies is highly dependent on continuous monitoring, education, and evaluation so that the incentives provided are truly on target and able to support sustainable national economic recovery.